Nursing care for coping with patients with Parkinson's disease - Silva, Clarissa da (2024)
bjective: The general objective of the study is to describe the care of patients with Parkinson's disease. Methodology: The integrative bibliographic review research with a qualitative approach resulted in a more detailed matrix presenting a total of 10 articles. Results: In this way, the work provided a comprehensive and in-depth view of the nursing care necessary to effectively cope with Parkinson's disease, incorporating updated knowledge from the literature, a detailed description of the disease, the importance of the social support network and the strategies adopted by patients to face the challenges inherent to the disease. Conclusion: The assistance provided by a nurse specialized in Parkinson's disease helps to reduce motor symptoms and improve the quality of life of patients, as the nurse, in addition to directing the care plan to meet the needs of the patient and their family, he guides the patient in the search for autonomy, always respecting their limits and complexities. Therefore, the quality of life of individuals with Parkinson's Disease is directly proportional to the specialized care provided by nurses.